A Pragmatic Analysis of Slogan Used in Cellular-Phone Advertisement and Its Application in Teaching Grammar in Junior High School - Rohmawati M, Irma (Scripta : English Department Journal, 2019)
The objective of the study is to find out linguistic forms and pragmatic meaning of slogan used in cellular – phone advertisement. The subject of this research is cellular – phone advertisement slogan that consisted of 33 slogans of cellular-phone. This research belongs to descriptive qualitative, it means the researcher uses descriptive data in the form of words written or spoken of the person, the result shows that there are six linguistic forms used in cellular phone slogans as follows: noun phrase 51,51%, verb phrase 21,21%, adjective phrase 6,06%, gerund phrase 9,09%, imperative sentence 6,06%, declarative sentence 6,06%. Pragmatic meaning results are as follow: asserting meaning 42,42%, persuading meaning 9,09 %, informing meaning is 12,12%.An application of research analysis can be used for the eight grade junior high school students on semester 2.